1986
DOI: 10.1007/bf02679607
|View full text |Cite
|
Sign up to set email alerts
|

Study on the oxidative rate and prooxidant activity of free fatty acids

Abstract: Oleic, linoleic and linolenic acids were autoxidized more rapidly than their corresponding methyl esters. Addition of stearic acid accelerated the rate of autoxidation of methyl linoleate and the decomposition of methyl linoleate hydroperoxides. Therefore, the higher oxidative rate of FFA's than their methyl esters could be due to the catalytic effect of the carboxyl groups on the formation of free radicals by the decomposition of hydroperoxides. Addition of stearic acid also accelerated the oxidative rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
2
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(163 citation statements)
references
References 19 publications
13
145
2
3
Order By: Relevance
“…Pacheco-Aguilar et al (2000) have reported that, lipases and phospholipases hydrolyze glycerol-fatty acid to release free fatty acids. Free fatty acids have been shown to oxidize faster than their triacylglycerols (Labuza et al 1969;Yanishlieva-Maslarova 1985) and faster than ethyl and methyl esters (Miyashita and Takagi 1986). Thus the free fatty acids exert a pro-oxidative effect.…”
Section: Changes In Free Fatty Acids (Ffa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pacheco-Aguilar et al (2000) have reported that, lipases and phospholipases hydrolyze glycerol-fatty acid to release free fatty acids. Free fatty acids have been shown to oxidize faster than their triacylglycerols (Labuza et al 1969;Yanishlieva-Maslarova 1985) and faster than ethyl and methyl esters (Miyashita and Takagi 1986). Thus the free fatty acids exert a pro-oxidative effect.…”
Section: Changes In Free Fatty Acids (Ffa)mentioning
confidence: 99%
“…Thus the free fatty acids exert a pro-oxidative effect. This effect is due to complex formation between hydroperoxides and carboxyl groups through a hydrogen bond, which results in an accelerated decomposition of hydroperoxides into free radicals (Miyashita and Takagi 1986). Bimbo (1998) has suggested a maximum acceptable value of 5 % as quality specifications for crude fish oil.…”
Section: Changes In Free Fatty Acids (Ffa)mentioning
confidence: 99%
“…While the formation of FFA itself does not lead to nutritional losses, its assessment is deemed important when considering the development of rancidity. Thus, a pro-oxidant effect of FFA on lipid matter has been proposed and explained on the basis of a catalytic effect of the carboxyl group on the formation of free radicals by the decomposition of hydroperoxides (Miyashita and Takagi, 1986;Aubourg, 2001). In addition, FFA are known to oxidize faster than higher-molecular weight lipid classes (namely, triglycerides and phospholipids) by providing a greater accessibility (lower steric hindrance) to oxygen and other prooxidant molecules (Labuza, 1971).…”
Section: Lipid Hydrolysis and Oxidation In Farmed Gilthead Seabream (mentioning
confidence: 99%
“…Formation of FFA itself does not lead to nutritional losses. However, it has been proven that accumulation of FFA in frozen fish is related to some extent with lack of acceptability of frozen fish, because FFA are known to cause texture deterioration by interacting with proteins (Mackie, 1993;Sotelo et al, 1995) and have shown to be strongly interrelated with lipid oxidation (Miyashita and Takagi, 1986;Han and Liston, 1988).…”
Section: Medinamentioning
confidence: 99%